El procedimiento para que se dicte el apremio personal total por pensiones alimenticias atrasadas limita asegurar el derecho a la prestación de alimentos y se vulnera el principio de simplificación y del interés superior del niño - Granda Salinas, Nadia del Pilar (2023)
The following research work is entitled "The procedure for the issuance of the total personal constraint for overdue alimony limits to ensure the right to the provision of food and violates the principle of simplification and the best interest of the child". This research work has been developed since the number of debtors of the Council of the Judiciary has increased throughout the country for non-alimony payments, putting the interests of the beneficiaries of food at risk, violating the best interest of the child principle. Due to the entire procedure involved in obtaining a restraining order, it is difficult to apply this coercive measure, as it is intended to force the beneficiary to cancel alimony obligations. However, with the multiple opportunities that are included in article 137 of the Organic Code of Processes, the only thing it provokes is the easiest way for the payer to avoid meeting his obligations. Moreover, to carry out this research, materials and methods were applied which allowed the development of the investigation; Interviews and surveys were conducted with legal professionals, specifically in the field of family law, results that served to verify the main and specific objectives, oriented to the need to abolish the procedure for obtaining a restraining order, in order to make a recommendation to legislators, based on simplifying the procedure, eliminating certain procedural actions that only delay the procedure, thus protecting the best interests of the child, the principle of effective protection of rights and legal certainty.